Evaluation of the Effects of Acute Cisplatin Administration on Testicular and Ovarian Tissue in Rats - Arzu Yay; Gözde Özge Önder; Özge Cengiz Mat; Sedat Çarkıt; Kübra Tuğçe Kalkan; Betül Yalçın (Düzce Tıp Fakültesi Dergisi)
Aim: Cisplatin, one of the effective chemotherapeutics in cancer treatment, has the potential to affect the testis and ovary, leading to permanent or temporary infertility. This study aimed to determine the acute effects of cisplatin on testis and ovary histology and to investigate whether it induces any changes in immunohistochemical cyclooxygenase-2 (COX2), nuclear factor kappa B p65 (NFκB-p65), and heat-shock protein 70 (HSP70) levels.Material and Methods: The study was planned as four groups: male control, male cisplatin, female control, and female cisplatin. The cisplatin group rats were adminestered with 7 mg/kg cisplatin, and all rats were sacrificed 24 hours later. Hematoxylin-eosin and Masson's trichrome stains were applied to testis and ovary tissues to examine their histopathological structure, and an immunohistochemistry staining protocol was applied to determine immunostaining intensity of COX2, NFκB-p65, and HSP70.Results: In the cisplatin group, a decrease in seminiferous tubule epithelium, an elevation in fibrotic response in the interstitial area, and a notable reduction in Johnson testicular biopsy score (p